Seasonal analysis of cloud-to-ground lightning flash activity in the Western Antarctica - Yusop, Norbayah; Abdullah, Mardina; Ahmad, Mohd Riduan; Mohd Esa, Mona Riza; Mohammad, Sulaiman Ali; Suparta, Wayan; Gulisano, Adriana Maria; Cooray, Vernon (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
: This paper presents a seasonal analysis of cloud-to-ground (CG) lightning flash activity in the Western Antarctica using a lightning detector sensor installed at the Carlini Base station. Data obtained from the detection system between February and December 2017 were analyzed. Three common locations and areas of composite active thunderstorms (labelled storm regions A, B, and C) were detected by the sensor within a 1000 km radius from the station. Storm region A was located to the northwest (N/W) of the station and covered the Amundsen/Bellingshausen Sea (ABS), whereas storm region C was located on the southeastern (S/E) side of the station over the Weddell Sea (WS), with distances ranging from 500 to 800 km and bearings of 270◦ to 360◦ and 90◦ to 180, respectively. Storm region B was located around 100 km from the station with the bearings of stroke taken from 0◦ to 360◦. A total of 2,019,923 flashes were detected, of which 43.01% were positive CG and 56.99% were negative CG flashes. The analysis revealed that more than 96% of the CG flashes (both positive CG and negative CG) were produced during the summer and fall seasons as compared with less than 4% during the winter and spring seasons. Most detected lightning strokes (>85%) were located in the central area around the station produced by storm region B and less than 15% were produced by storm region A and storm region C, located in the ocean areas over the Amundsen/Bellingshausen Sea and the Weddell Sea.